The Image of the Creator in Ibn Rashiq’s Book “Al Omda” - Alhourani, Mohammad Issa (Opción, 2019)
The aim of the study is to investigate the image of the creator inIbn Rashiq’s book entitled Al Omda via comparative qualitativeresearch methods. As a result, the creator does not depart far from hislinguistic meaning, through which he tries to capture thepsychological, existential and intellectual aspects. In conclusion, IbnRashiq was largely consistent with critics of his time; his view came tothe creator - like other old critics - focused on the psychological, moraland ethical aspects.